Welfare Improvement Models and Strategies through Dissemination of Family Planning Information in the Remote Indigenous Community of Baduy - Ahmad Sihabudin; Idi Dimyati; Melati Mediana Tobing (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
There are many types of  contraceptives used by the Baduy remote indigenous communities (Baduy KAT) in Lebak regency, Banten, West Java, Indonesia. According to data, the number of family planning acceptors among the Baduy community stood at 1,529 in February 2021 comprising 1,503 in Outer Baduy and  26  in Inner Baduy. In the beginning, most Baduy KAT used implants before they changed contraceptives  of their  choice. This study aims to reveal what channels are used to disseminate information about family planning, as well as to ensure the effectiveness of the innovations about family planning information they receive. The method used is explanatory survey, with a frequency distribution to analyze and determine the relationship between variables and  Spearman correlation analysis. The results showed that most respondents or 49% received family planning information from their relatives, 22% received it  from health workers (posyandu cadres), 21% received it  from village officials, 7% received it from  indigenous community leaders (kakolot), and only 1%  received it  from the media. This study found that there is a fairly strong relationship between communication channels and the effectiveness of innovation acceptance. Most of the respondents stated that they decided to accept the family planning innovations concept within 6 months by using humans as a communication channel, such as their relatives, health workers, village officials, and kakolot leaders.